Quantitative Computed Tomography Assessment of Pectoralis and Erector Spinae Muscle Area and Disease Severity in Chronic Obstructive Pulmonary Disease Referred for Lung Volume Reduction. (4th March 2021) - Attaway, Amy H.; Welch, Nicole; Yadav, Ruchi; Bellar, Annette; Hatipoğlu, Umur; Meli, Yvonne; Engelen, Marielle P. K. J.; Zein, Joe; Dasarathy, Srinivasan
Abstract: Patients with advanced chronic obstructive pulmonary disease (COPD) develop skeletal muscle loss (sarcopenia) that is associated with adverse clinical outcomes including mortality. We evaluated if thoracic muscle area is associated with clinical outcomes in patients with severe COPD. We analyzed consecutive patients with severe COPD undergoing evaluation for lung volume reduction from 2015 to 2019 ( n  = 117) compared to current and former smoking controls undergoing lung cancer screening with normal lung function ( n  = 41). Quantitative assessments of pectoralis muscle (PM) and erector spinae muscle (ESM) cross sectional area (CSA) were related to clinical outcomes including composite endpoints. Our results showed a reduction in PM CSA but not ESM CSA was associated with the severity of GOLD stage of COPD. Current smokers demonstrated reduced PM CSA which was similar to that in COPD patients who were GOLD stages 3 and 4. PM CSA was associated positively with FEV1, FEV1 % predicted, FVC, DLCO, and FEV1 /FVC ratio, and was associated negatively with the degree of radiologic emphysema. ESM correlated positively with DLCO, RV/TLC (a marker of hyperinflation), and correlated negatively with radiologic severity of emphysema. Kaplan-Meier analysis showed that reductions in PM but not ESM CSA was associated with the composite end point of mortality, need for lung volume reduction, or lung transplant. In conclusion, in well-characterized patients with severe COPD referred for lung volume reduction, PM CSA correlated with severity of lung disease, mortality, and need for advanced therapies. In addition to predicting clinical outcomes, targeting sarcopenia is a potential therapeutic approach in patients with severe COPD.